Draft genome sequence of Staphylococcus aureus KT/312045, an ST1-MSSA PVL positive isolated from pus sample in East Coast Malaysia - Zarizal, Suhaili; Yeo, Chew Chieng; Noor Muzamil, Mohamad (2016)
Most of the efforts in elucidating the molecular relatedness and epidemiology of Staphylococcus aureus in Malaysia have been largely focused on methicillin-resistant S. aureus (MRSA). Therefore, here we report the draft genome sequence of the methicillin-susceptible Staphylococcus aureus (MSSA) with sequence type 1 (ST1), spa type t127 with Panton-Valentine Leukocidin (pvl) pathogenic determinant isolated from pus sample designated as KT/314250 strain. The size of the draft genome is 2.86 Mbp with 32.7% of G + C content consisting 2673 coding sequences. The draft genome sequence has been deposited in DDBJ/EMBL/GenBank under the accession number AOCP00000000.